The shotgun method the demography of the ancient Greek city-state culture - Hansen, Mogens Herman, 1940- (Fordyce W. Mitchel Memorial Lecture Series., 2006)
"Reflecting the innovative work of the Copenhagen Polis Centre's 2004 inventory of Archaic and Classical Greek city-states, Hansen's "shotgun method" for reconstructing and estimating the overall size and local distribution of the Greek population challenges the long-standing opinion that the majority of ancient Greeks lived a rural, subsistent life"--Provided by publisher.